Differential Expression of MicroRNAs in Chronic Obstructive Pulmonary Disease - Kara, Murat; Kirkil, Gamze; Kalemci, Serdar (Wroclaw Medical Univ, 2016)
Background. This study aimed to investigate the associations of miRNA with COPD patients. Objectives. Chronic obstructive pulmonary disease (COPD) is characterized by progressive and largely irreversible airflow limitation. COPD is one of the most common causes of death globally and it is still a serious public health problem worldwide. Pathogenesis of COPD is multifactorial including genetics and environmental factors. Material and Methods. Sixty patients who were diagnosed with COPD according to GOLD guidance and 40 controls were involved in the study. This study was separated into four groups according to GOLD guidance. miR_16, miR_17, miR_29c, miR_92, miR_125, miR_126, miR_146, miR_155, miR_181, mir_122 expressions from the total miRNAs obtained were worked on by using real time-PCR method. The p-values are calculated based on a Student's t-test of the replicate 2(boolean AND) (-Delta Ct) values for each gene in the control group. Results. The miRNAs expressions in normal and COPD patients were found differentially. The miR-29c (p = 0.043) and -126 (p = 0.012) were found significantly different compared to control group. When their expressions are evaluated according to stage, miR-92 expression showed down regulation stage II and no change was observed in other miRNAs. miR-29c and miR-126 expressions showed significant differences in stage III and only miR-126 expression showed significant difference in stage IV. Conclusions. These results show that miRNA evaluations may give information about the diagnosis, staging and prognosis of the disease. In this study, we demonstrated that miR-29c and -126 are essential for the development of COPD
Keywords: COPD; MicroRNAs; smoking cigarettes